Socio-demographic characteristics and tobacco use among the adults in urban slums of Dhaka, Bangladesh - Khandker, Nusrat Nausheen; Biswas, Tuhin; Khan, Abdullah Nurus Salam; Hasib, Enamul; Rawal, Lal Bahadur (© 2017 BioMed Central Ltd., 2018)
This article was published in the Tobacco Induced Diseases [© 2017 The Author(s).] and the definitive version is available at: https://doi.org/10.1186/s12971-017-0131-1 The Journal's website is at: http://www.tobaccoinduceddiseases.org/Socio-demographic-characteristics-and-tobacco-use-among-the-adults-in-urban-slums,75897,0,2.html